Femoral osteochondroplasty can be performed effectively without the risk of avascular necrosis or femoral neck fractures in an experimental ovine FAI model. Issue 1 (January 2018) - Schmaranzer, F.; Arendt, L.; Lerch, T.D.; Steppacher, S.D.; Nuss, K.; Wolfer, N.; Dawson, H.E.; von Rechenberg, B.; Kircher, P.R.; Tannast, M.
Summary: Objective: The experimental induction of cam-type femoroacetabular impingement (FAI) in sheep is established. To tap the full potential of this ovine model, one should be able to perform a femoral osteochondroplasty safely. This study was based on previous cadaver experiments on the blood supply to the ovine femoral head and on the biomechanical strength of the proximal femur following offset creation. We hypothesized that offset creation in this ovine FAI model does not lead to (1) avascular necrosis (AVN) of the ovine femoral head or (2) iatrogenic femoral neck fractures and (3) can be performed effectively. Design: In this experimental, controlled, prospective study nine sheep underwent unilateral FAI induction through an intertrochanteric, varus osteotomy. Seventy days following FAI induction, femoral osteochondroplasty was performed. Sheep were sacrificed after another 140 days. Radiographs, computed tomography (CT) scans and MRI were acquired. Histologic samples were stained with hematoxylin-eosin. (1) The multimodal Association Research Circulation Osseous (ARCO) classification was used for assessment of AVN. (2) Femoral neck fractures were assessed with the multimodal imaging approach. (3) Pre- and postoperative (=after sacrifice) alpha angles and femoral neck diameters were compared. Results: (1) No signs for AVN according to the ARCO classification or (2) for femoral neck fractures were detected. (3) Mean alpha angles and femoral neck diameters decreased significantly (p < 0.001) superiorly by at least 30° respectively 4 mm after the offset creation. Conclusions: Femoral osteochondroplasty can be performed effectively and without the risk of AVN or femoral neck fractures in this ovine FAI model.